Leptin and its receptor in hematologic malignancies - Han, Tian-Jie (Int J Clin Exp Med, 2015)
Leptin is an adipocyte-derived cytokine coded by the obese gene, not only regulates metabolism, but also participates in hematopoiesis. Aberrant leptin levels in patients with hematologic malignancies were observed and associates with clinical characters, such as body mass index (BMI), gender, blast cell percentage. Leptin concentrations alter while diseases progress or remission. Leptin receptor is expressed in hematopoietic CD34+ stem cells, erythrocytes, lymphocytes, blast cells and samples in leukemia and lymphoma patients. The adipokine stimulates cell proliferation, cytokine secretion and protects malignant cells from apoptosis through Janus kinase-signal transducer and activator of transcription (JAK-STAT), mitogen-activated protein kinase and extracellular signal activated kinase 1/2 (MAPK/ERK1/2), or 3 kinase (PI3K) signaling pathways. These findings indicate leptin signaling possibility take part in occurrence, progression and prognosis of hematologic malignancies. This article reviews leptin/leptin receptor expression and the correlations with clinical characters, treatment and prognosis in myeloid and lymphoid neoplasms.